Α‐Synuclein Deposition in Sympathetic Nerve Fibers in Genetic Forms of Parkinson's Disease. Issue 10 (2nd June 2021) - Isonaka, Risa; Goldstein, David S.; Zhu, William; Yoon, Esther; Ehrlich, Debra; Schindler, Alice B.; Kokkinis, Angela D.; Sabir, Marya S.; Scholz, Sonja W.; Bandres‐Ciga, Sara; Blauwendraat, Cornelis; Gonzalez‐Alegre, Pedro; et al.
Abstract: Background: Cytoplasmic inclusions of α‐synuclein (α‐syn) in brainstem neurons are characteristic of idiopathic Parkinson's disease (PD). PD also entails α‐syn buildup in sympathetic nerves. Among genetic forms of PD, the relative extents of sympathetic intraneuronal accumulation of α‐syn have not been reported. Objective: This cross‐sectional observational study compared magnitudes of intraneuronal deposition of α‐syn in common and rare genetic forms of PD. Methods: α‐Syn deposition was quantified by the α‐syn‐tyrosine hydroxylase colocalization index in C2 cervical skin biopsies from 65 subjects. These included 30 subjects with pathogenic mutations in SNCA (n = 3), PRKN [biallelic (n = 7) and monoallelic (n = 3)], LRRK2 (n = 7), GBA (n = 7), or PARK7/DJ1 [biallelic (n = 1) and monoallelic (n = 2)]. Twenty‐five of the mutation carriers had PD and five did not. Data were also analyzed from 19 patients with idiopathic PD and 16 control participants. Results: α‐Syn deposition varied as a function of genotype (F = 16.7, P  < 0.0001). It was above the control range in 100% of subjects with SNCA mutations, 100% with LRRK2 mutations, 95% with idiopathic PD, 83% with GBA mutations, and 0% with biallelic PRKN mutations. α‐Syn deposition in the biallelic PRKN group was significantly higher than in the control group. In addition, patients with biallelic PRKN mutations had higher α‐syn deposition than their unaffected siblings. Conclusions: Individuals with SNCA, DJ‐1, LRRK2, or GBA mutations have substantial intraneuronal α‐syn deposition in sympathetic noradrenergic nerves in skin biopsies, whereas those with biallelic PRKN mutations do not. Biallelic PRKN patients may have mildly increased α‐syn deposition compared with control subjects. © 2021 International Parkinson and Movement Disorder Society